2020
DOI: 10.1155/2020/1978043
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Mechanism of Sarsasapogenin in Treating Precocious Puberty by Regulating the HPG Axis

Abstract: The present study aims to investigate the effects and mechanisms of sarsasapogenin resistance to precocious puberty. Female Sprague Dawley rats were divided into a normal (N) group, model (M) group, leuprolide (L) group, and sarsasapogenin (Sar) group. Rats at 5 days of age were given a single subcutaneous injection of 300 micrograms of danazol to establish the precocious puberty model. After 10 days of modeling, drug intervention was started. The development of the uterus and ovary was observed by hematoxylin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…In rat model of PP, increased KISS1 and GPR54 expression was also observed following danazol treatment. However, GPR54 expression was not affected by sarsasapogenin, another active ingredient from A. asphodeloides, although it has anti-PP activity (Hu et al, 2020b). Apparently, the molecular mechanism of action of sarsasapogenin is different from the mechanism of action of TAIII, which downregulated KISS1 and GPR54 expression elevated by leptin treatment, suggesting that TAIII may exert anti-PP activity through the KISS1/GPR54 system.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In rat model of PP, increased KISS1 and GPR54 expression was also observed following danazol treatment. However, GPR54 expression was not affected by sarsasapogenin, another active ingredient from A. asphodeloides, although it has anti-PP activity (Hu et al, 2020b). Apparently, the molecular mechanism of action of sarsasapogenin is different from the mechanism of action of TAIII, which downregulated KISS1 and GPR54 expression elevated by leptin treatment, suggesting that TAIII may exert anti-PP activity through the KISS1/GPR54 system.…”
Section: Discussionmentioning
confidence: 88%
“…For example, Zhibaidihuang decoction made with A. asphodeloides, Rehmannia glutinosa, Cornus officinalis, peony bark, yam, Poria cocos and Alisma orientalis was found to alleviate PP by reducing the levels of serum hormone FSH, LH and E 2 (Xu & Qiu, 2007;Yu et al, 2014). Sarsasapogenin, a steroidal sapogenin, is a main active ingredient in Zhimu (Bao et al, 2007) and was found to have anti-PP activity through inhibiting the HPGA (Hu et al, 2020a). In addition, pharmacological studies have shown that sarsasapogenin also has activities against thrombosis, Alzheimer's disease, tumor, inflammation, and depression (Han et al, 2018;Wang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…After PND 22, the vaginal opening was examined daily at 9:00, and vaginal smears were used to confirm whether the female offspring rats were entering a regular estrous cycle. [21] Vaginal cells were collected through saline lavage and observed under a microscope (Olympus CX23RTFS2, Japan).…”
Section: Vaginal Opening Examinationmentioning
confidence: 99%
“…The coefficient of each organ was calculated as follows: ([organ wet weight (g)/body weight (g)] × 10 −4 ). [21]…”
Section: Whole Blood Sample and Tissue Collectionmentioning
confidence: 99%
“…Therefore, the role of alternative therapies is important. Hu et al [ 27 ] investigated the effects of sarsasapogenin in treating precocious puberty by regulating the hypothalamus–pituitary–gonadal (HPG) axis. To establish the precocious puberty phase, 5 day old rats were given a single subcutaneous injection of danazol (300 µg).…”
Section: Biological Properties Of Sarsasapogeninmentioning
confidence: 99%